PERFIL E NÍVEL DE ESPERANÇA ENTRE PACIENTES QUE REALIZAM HEMODIÁLISE E DIÁLISE PERITONEAL - Rayane Alves Moreira; Moema da Silva Borges (Universidade Federal do Paraná, 2020)
Objective: To identify the clinical and psychosocial profile and measure the level of hope of patients undergoing hemodialysis and peritoneal dialysis. Method: Exploratory, descriptive and quantitative study conducted in a renal unit in Distrito Federal with patients undergoing dialysis. Data was collected in September and October 2018 with the use of a characterization questionnaire and the application of the Herth Hope Index (HHI). Mann-Whitney test was used for comparison of the levels of hope. Results: Overall, 122 patients participated in the study. The average hope score obtained was 39.79 (± 5.3) and the highest value was 48. A comparative test showed no significant difference between the levels of hope. Conclusion: Despite all the limitations imposed by treatment and illness, this population has a high level of hope. The present study contributed to the expansion of scholarly debate, which allowed the identification and establishment of the key elements of an effective planning of nursing care, especially in the context of the treatment of chronic kidney disease.